Influence of environmental factors on the growth and reproduction of Pistia stratiotes L. - Mohamed Sbaghi; Mohamed El Aalaoui (African and Mediterranean Agricultural Journal - Al Awamia)
Pistia stratiotes L. is an aquatic plant widely found in freshwater ecosystems. This study investigates how temperature, photoperiod, fertilizer, and salinity affect its growth and reproductive success. The results showed that higher temperatures led to faster developmental stages, with germination taking 5.9 days at 30°C compared to 11.9 days at 20°C. Photoperiod treatments influenced germination success, with 16L:8D treatment resulting in a shorter duration (6.0 days) compared to 12L:12D (7.7 days) and continuous light (8.9 days). The 12:7:7 N:P:K fertilizer treatment yielded the most favorable outcomes, with the highest survival rate from germination to plant reproduction (96.2%), improved growth (18.0 cm leaf length, 18.8 cm leaf width, 45.4 cm plant height, 6.4 g dw root biomass), and increased biomass accumulation (13.5 g dw total biomass) compared to the 7N-15P-15K treatment. Regarding salinity, exposure to undiluted seawater or a 50% dilution severely limited germination and growth. However, a 5% dilution of seawater or freshwater allowed the plant to complete its full life cycle. The freshwater treatment resulted in a life cycle duration of 141.1 days, while the 5% seawater dilution achieved a duration of 135.6 days. In conclusion, this study elucidates the pivotal role of temperature, photoperiod, and fertilization in shaping the developmental duration, biometrics, and reproductive parameters of P. stratiotes. Understanding these environmental influences is crucial for effective cultivation and management of this species in diverse ecological settings.